The impact of music festivals on the local community and the local hospitality industry : the Malaysian context / Nur Afifah Binti Khairuddin - Khairuddin, Nur Afifah (Faculty of Art and Design, 2013)
The purpose of this study is to examine the impact of music festivals on local comunity and the local hospitality industry. This academic writing will emphasize the impact of music festivals and the local hospitality industry, and in particularly, in Malaysia. In this case, to make people think positively about music festival. Successful festivals involve in most cases an additional income for the organizer body and other stakeholders within the industry, but eventually these kinds of events could cause negative impact especially to the local community that hosts them. That is the reason why the organizers have to focus on local sustainability and in protecting the local community. This is further supported by highliting the positive impact of music.